Factors influenced employees turnover intention in KIP Hotel Kuala Lumpur / Aainaa Nortarmizi - Nortarmizi, Aainaa (Faculty of Business and Management, 2017)
This paper examines on employee turnover intention and the relationship with job satisfaction, job performance, and workplace environment. This study highlights and defines basic concepts of job satisfaction, job performance and workplace environment and employee turnover intention. The idea of Employee Turnover Intention is becoming hot topic for multinational, domestic and local organization, even in the government organization’s and private companies. As the studies which already did by researcher, so the main purpose of this study to check the influenced of Job Satisfaction, Job Performance and Workplace Environment among employees in KIP Hotel Kuala Lumpur, Malaysia. Besides that, the result proved that job performance is the most influenced factor employee turnover intention is job performance by 44.5%. The total sample size of the respondents was collected from 150 respondents, so then the data was processed by using multiple regression software.